Performa Reproduksi Ternak Pada Dataran Tinggi (Studi Kasus Di Koto Baru Hiang Kecamatan Sitinjau Laut Kabupaten Kerinci) - Melli Sri Wahyuni (Jurnal Ilmu Peternakan Indonesia, 2026)
Local cattle are a vital commodity for supporting food security and the economy of Indonesian communities. However, the productivity of local cattle remains relatively low, partly due to suboptimal reproductive performance. Environmental factors—specifically geographical variations such as high-altitude terrain—are believed to influence livestock reproductive performance. This study aims to assess the reproductive performance of cattle and the success rate of artificial insemination (AI) in Dusun Baru Hiang, Sitinjau Laut District, Kerinci Regency. The research was conducted within an integrated smallholder farming system involving 100 cattle managed by approximately 50 farmers. The parameters observed included Body Condition Score (BCS), Services per Conception (S/C), Conception Rate (CR), gestation length, Calving Interval (CI), and Days Open (DO). Data were collected through direct field observation, farmer interviews, and the recording of reproductive data, followed by descriptive analysis. The findings are expected to provide insights into the reproductive performance of local cattle raised in highland areas and the success rate of artificial insemination implementation. This study is intended to serve as a source of information and a reference for farmers and relevant stakeholders in efforts to improve the reproductive performance and productivity of cattle in highland regions.